Critical Analysis of Innovations in Dental Surgery and Technology - Aldablan, Osama Saud; Alhokail, Mojahd riyadh; Alnashi, Faisal Fahad; Alayoubi, Wael Adnan; Alqahtani, Nasser Mushabbab; Fedah, Ibrahim Mohammed; Aljayzani, Sultan Ali; Aleidan, Faisal Abdulaziz; Alotaibi, Mashhour Awwadh; Alqarni, Amal Fehaid; Alharbi, Abdulelah Abdullah (Journal of Ecohumanism, 2024)
Advancements in dental surgery solutions and techniques have greatly changed the face of oral surgeries. Due to the constant development of technology in the dental field, minimally invasive surgical methods, and the addition of artificial intelligence, dental treatments are less time-consuming and more accurately performed for patients. Consequently, this paper aims to assess the extent to which the major technological advances in dental surgery have affected clinical practices and examine difficulties occasioned by these new developments. The paper also describes how these innovations can enhance the surgery, patients, and results. Finally, suggestions for improving the implementation of these innovations in clinical environments are presented.